Implementation of Formative Assessment in Physics Learning to Improve Students' Conceptual Understanding - Nabila, Putri; Wahyuni, Veni; Festiyed, Festiyed; Emillianur, Emillianur (Universitas Lambung Mangkurat, 2024)
This research examines the application of formative assessment to physics learning to increase students' conceptual understanding. This literature review includes publications from 2014 to 2024 taken from Google Scholar and GARUDA, with 14 articles taken with appropriate criteria. The research results show that using technology-based formative assessments, such as Google Forms, TikTok videos, multimedia modules, and web-assisted assessment systems, effectively increases students' conceptual understanding and motivation. This approach provides fast and precise feedback, identifies misconceptions, and supports students' scientific argumentation abilities. Overall, applying formative assessment and integrating technology in physics learning is important in deepening students' understanding of concepts.